Binding Molecules in Tick Saliva for Targeting Host Cytokines, Chemokines, and Beyond - Desidério, Chamberttan Souza; Flávio-Reis, Victor Hugo Palhares; Pessoa-Gonçalves, Yago Marcos; Tiveron, Rafael Destro Rosa; Sales-Campos, Helioswilton; Felice, Andrei Giacchetto; Soares, Siomar de Castro; Guillermo-Ferreira, Rhainer; Rodrigues, Wellington Francisco; Oliveira, Carlo José Freire (Biomolecules (Basel, Switzerland), 2024)
Ticks have coevolved with their hosts over millions of years, developing the ability to evade hemostatic, inflammatory, and immunological responses. Salivary molecules from these vectors bind to cytokines, chemokines, antibodies, complement system proteins, vasodilators, and molecules involved in coagulation and platelet aggregation, among others, inhibiting or blocking their activities. Initially studied to understand the complexities of tick–host interactions, these molecules have been more recently recognized for their potential clinical applications. Their ability to bind to soluble molecules and modulate important physiological systems, such as immunity, hemostasis, and coagulation, positions them as promising candidates for future therapeutic development. This review aims to identify the binding molecules present in tick saliva, determine their primary targets, and explore the tick species involved in these processes. By associating the binding molecules, the molecules to which they bind, and the effect caused, the review provides a basis for understanding how these molecules can contribute to possible future advances in clinical applications.